The Framework of Islamic Educational Management to Improve Quality of Graduates - Novita, Mona; Madyan, Madyan; Sukatin, Sukatin (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2021)
This study analyzed 1) the management of the basic components of Islamic education; 2) the construction of a curriculum management framework for enhancing the quality of Indonesian graduates; and 3) assess the role of IQF as the current Higher Education Curriculum in resolving the difficulties with Indonesian graduate quality. This study takes the form of a literature review that is explained qualitatively. Based on the findings of the investigations, the following conclusions can be drawn: 1) management of the basic components of Islamic educational, which include: (a) management of Islamic education personnel, (b) management of Islamic education students, (c) management of Islamic education curriculum, (d) Islamic education financial management, and (e) management of Islamic education facilities and infrastructure; 2) building a curriculum management framework for enhancing the quality of Indonesian graduates, which will include the following stages: (a) planning, (b) implementation, and (c) curriculum evaluation; and 3) it is envisaged that the IQF policy will help to improve the quality of Indonesian graduates.